Analysis of Senior High School Students' Science Literacy in Understanding Static Fluids - Nora Indrasari (Master of Physics Education Study Programme, 2025)
This article aims to identify the scientific literacy skills of high school students in static fluid material. This type of research is quantitative descriptive with a study sample of 136 high school 12th grade students. The data collection technique is a test instrument in the form of 10 multiple choice questions reasoned had 0.741 reliability. The test results showed that the scientific literacy ability test scores of students with static fluid material were 16% at the SI level, 4% at the NSL level, 40% at the FSL level, 38% at the level CSL, and 2% at the MSL level.